(untitled) (Conferencea, 2022)
The idea of the perfect man is the idea of the Supreme Lord, which has both national and universal significance, embodies the highest spiritual and physical perfection of mankind, and always encourages him to goodness. is an idea that has inspired unparalleled achievements in the field of spirituality and enlightenment. Emphasizing the importance of the idea of the perfect man in the education of young people is one of the most pressing issues today. That is why we should be concerned about the upbringing of harmoniously developed generations so that young people grow up spiritually and physically mature in all respects.